Gpr18 agonist dampens inflammation, enhances myogenesis, and restores muscle function in models of Duchenne muscular dystrophy - Dort, Junio; Orfi, Zakaria; Fiscaletti, Melissa; Campeau, Philippe M.; Dumont, Nicolas A. (Frontiers in Cell and Developmental Biology, 2023)
Muscle wasting in Duchenne Muscular Dystrophy is caused by myofiber fragility and poor regeneration that leads to chronic inflammation and muscle replacement by fibrofatty tissue. Our recent findings demonstrated that Resolvin-D2, a bioactive lipid derived from omega-3 fatty acids, has the capacity to dampen inflammation and stimulate muscle regeneration to alleviate disease progression. This therapeutic avenue has many advantages compared to glucocorticoids, the current gold-standard treatment for Duchenne Muscular Dystrophy. However, the use of bioactive lipids as therapeutic drugs also faces many technical challenges such as their instability and poor oral bioavailability. Here, we explored the potential of PSB-KD107, a synthetic agonist of the resolvin-D2 receptor Gpr18, as a therapeutic alternative for Duchenne Muscular Dystrophy. We showed that PSB-KD107 can stimulate the myogenic capacity of patient iPSC-derived myoblasts in vitro. RNAseq analysis of revealed an enrichment in biological processes related to fatty acid metabolism, lipid biosynthesis, small molecule biosynthesis, and steroid-related processes in PSB-KD107-treated mdx myoblasts, as well as signaling pathways such as Peroxisome proliferator-activated receptors, AMP-activated protein kinase, mammalian target of rapamycin, and sphingolipid signaling pathways. In vivo, the treatment of dystrophic mdx mice with PSB-KD107 resulted in reduced inflammation, enhanced myogenesis, and improved muscle function. The positive impact of PSB-KD107 on muscle function is similar to the one of Resolvin-D2. Overall, our findings provide a proof-of concept that synthetic analogs of bioactive lipid receptors hold therapeutic potential for the treatment of Duchenne Muscular Dystrophy.